Knowledge, attitude and practices of general practitioners about use of antiviral drugs in viral infections other than HIV - Beri, Shirish G.; Bhide, Harshavardhan S.; Dhande, Priti P.; Raman, Aishwarya (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Antiviral drugs for viral infections other than HIV are effective only for hepatitis, herpes and influenza. It has been observed that general practitioners (GPs) treat viral infections with antibiotics. The use of antibiotics in viral infections is not rational. Hence, authors conducted this study to assess the Knowledge, Attitude and Practices of General Practitioners (GPs) about treatment of viral infections other than HIV. Methods: It was a descriptive, observational, cross- sectional study among 100 GPs in Southern Pune. A pretested questionnaire was used to assess their knowledge, attitude and practices about treatment of viral infections other than HIV. Prior informed written consent was taken from the GPs who were grouped under MBBS, BHMS and BAMS categories according to their qualifications. Correct answers among these groups were analysed using chi-square test, Spearman’s coefficient test and ANOVA. Results: The percentages of correct answers in the groups were comparable.56% GPs have poor knowledge of Influenza treatment.30-36% do not treat Herpes genitalis and zoster with antiviral drugs. Authors found that 44%, 30% and 28% of total GPs don’t have proper knowledge, attitude and practice respectively about common viral infections other than HIV and antiviral drugs. Conclusions: GPs are significantly unaware about rational use of antiviral drugs. They have poor knowledge about management of influenza.